Capo Mannu Project 2011 - Lithic Industry - Stefano Caruso; Davide D'Errico; Daniele Maffezzoli (Traces in Time, 2012)
The authors present the first results of the analysis carried out on the prehistoric lithic industry, collected during the systematic survey campaign of September 2011, in the coastal area of Capo Mannu, central western Sardinia, and coming from old collections from the same area.